Three-dimensional analysis of seminiferous tubules and spermatogenic waves in mice. Issue 5 (November 2017) - Nakata, Hiroki; Sonomura, Takahiro; Iseki, Shoichi
Abstract : The aim of the present study was to reconstruct seminiferous tubules and analyze spermatogenic waves in seminiferous epithelia in developing and adult mice using serial paraffin sections and high-performance three-dimensional (3D) reconstruction software. By labeling the basement membrane of seminiferous tubules with fluorescent immunohistochemistry or periodic acid-Schiff-hematoxylin staining, all seminiferous tubules were reconstructed in 9 testes from 9 different mice, 3 each at 0, 21 and 90 days (adult) postpartum. The 3D structure of seminiferous tubules, including the number and length of tubules as well as the number of connections with the rete testis, branching points and blind ends, was assessed accurately. Although tubules showed marked variations among individual mice, their overall structure was regular and retained from newborn to adult mice. Some seminiferous tubules contained inner portions running distant from the testis surface. In a representative testis at 21 days, the sites at which spermatids initially occurred were examined by labeling acrosomes and were found to be preferentially distributed in the upper and medial portions of the testis close to the rete testis. In a representative adult testis, 76 complete waves with an average length of 16.9 mm were found and their directions were analyzed. The methods used in the present study will be useful for investigating the structure and function of seminiferous tubules in mice and humans under normal and pathological conditions, such as infertility.